A systematic review of blockchain - Min Xu; Xingtong Chen; Gang Kou (Financial Innovation, 2019)
Blockchain is considered by many to be a disruptive core technology. Although many researchers have realized the importance of blockchain, the research of blockchain is still in its infancy. Consequently, this study reviews the current academic research on blockchain, especially in the subject area of business and economics. Based on a systematic review of the literature retrieved from the Web of Science service, we explore the top-cited articles, most productive countries, and most common keywords. Additionally, we conduct a clustering analysis and identify the following five research themes: "economic benefit," "blockchain technology," "initial coin offerings," "fintech revolution," and "sharing economy." Recommendations on future research directions and practical applications are also provided in this paper.
Keywords: 650; Blockchain; Systematic literature review; Business and economics; CiteSpace